2010
DOI: 10.1038/gt.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to adeno-associated virus type 2 encoding channelrhodopsin-2 in a genetically blind rat model for gene therapy

Abstract: We had previously reported that transduction of the channelrhodopsin-2 (ChR2) gene into retinal ganglion cells restores visual function in genetically blind, dystrophic Royal College of Surgeons (RCS) rats. In this study, we attempted to reveal the safety and influence of exogenous ChR2 gene expression. Adeno-associated virus (AAV) type 2 encoding ChR2 fused to Venus (rAAV-ChR2V) was administered by intra-vitreous injection to dystrophic RCS rats. However, rAAV-ChR2 gene expression was detected in non-target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 46 publications
1
40
0
1
Order By: Relevance
“…Thus far, studies assessing the feasibility of using microbial opsins for vision restoration have been carried out in small laboratory animals such as rodents, rabbits, and marmosets. [7][8][9][10]26,27 To our knowledge, the viral doses and construct optimizations necessary to obtain functional optogenetic readout have not yet been investigated in macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, studies assessing the feasibility of using microbial opsins for vision restoration have been carried out in small laboratory animals such as rodents, rabbits, and marmosets. [7][8][9][10]26,27 To our knowledge, the viral doses and construct optimizations necessary to obtain functional optogenetic readout have not yet been investigated in macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of lymphocyte subsets revealed that the ratio of CD4+/CD8+ T cells increased at 1 week after the injection (Sugano et al 2011 ). However, the ratio immediately returned to baseline and there was no change at any future time point.…”
Section: Systemic Analysis For Immune Reactionmentioning
confidence: 79%
“…In our experiments, we examined adhesive leukocytes in retinal blood vessels VEPs were recorded after ChR2 therapy, which had no recordable response before treatment. P1 latency was shortened after ChR2 therapy compared with normal rats due to the differences in the mechanism of light absorption in the retina (Sugano et al 2011 ). As our results indicate, there was no obvious infl ammation following the injection of AAV vector (control) or AAV-ChR2V (Fig.…”
Section: Immune Reaction In the Eyementioning
confidence: 96%
“…It is also important to note that with the exception of melanopsin, the photoswitches are either nonhuman proteins, like the algal/bacterial channelrhodopsins and halorhodopsins, or completely artificial, such as the ionotropic glutamate receptor (LiGluR), with the inherent uncertainty of whether they might present an increased immunogenicity, especially in the context of a degenerating retina, which may have less structural integrity than the immune-privileged healthy retina. A recent study 14 has attempted to address this issue in regard to the channelrhodopsin-2 gene (which originates from the algae, Chlamydomonas reinhardtii) delivered to the rodent retina using the adeno-associated virus (AAV)-2 vector. The authors concluded that although antibodies to rAAV and channelrhodopsin were detectable, their levels were too low for rejection.…”
Section: Overviewmentioning
confidence: 99%
“…While animal models have proven useful in exploring the visual restorative promise of optogenetic therapy, the field lacks a single animal model that embodies all the necessary biological features with which to best predict the complex phenotypic outcome in humans (e.g., human responses to therapy). To date, in the literature, all efficacy and toxicology evaluations 14 have been performed with the truncated channelrhodopsin-2 fused with a reporter such as green flourescent protein or Venus.…”
Section: A Proposed Human Clinical Trialmentioning
confidence: 99%